Pelatihan dan Pendampingan Inventarisasi Aset Sekolah Sebagai Keberlanjutan Lembaga Pendidikan di SD Muhammadiyah 8 Malang - Affan, Muhammad Wildan; Irawan, Dwi; Puja, Puteri Amelia; Rayis, Dzulhijah Alkayyis; Rani, Andini Esa Dewi; Fauziah, Shinta Nur (Fakultas Sains dan Teknik, Universitas Bangka Belitung, 2025)
A key component to ensuring the long-term sustainability of educational institutions is efficient asset management. The recording and administration of school assets at Muhammadiyah Elementary School 8